Listening & notetaking skills with audioscripts - Phylliss L. Lim (National Geographic Learning/Heinle Cengage Learning, 2014)
The new edition of the Listening and Notetaking Skills series incorporates engaging National Geographic content and video featuring authentic interviews and videos with National Geographic Explorers! This unique approach engages learners while enhancing listening comprehension and developing notetaking and study skills